Migrant remittances: Alternative money transfer channels - Martina Metzger; Tim Riedler; Jennifer Pédussel Wu (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2019)
This paper first explores the role of digital financial services, e.g. mobile money systems and cryptocurrency-based systems, and their impact on the choice of migrants to send remittances. Secondly we discuss whether alternative remittances sending channels increase access to financial services for remittance-sending and remittance-receiving households. Africa, and in particularly Kenya, are pioneers in alternative money transfer systems and of tailor-made regulatory initiatives to address digital financial services. Thus, our paper focuses on the technologies of the Kenyan mobile money system, M-Pesa, and the major cryptocurrency, Bitcoin, and based on that takes into account selected experiences of other Sub-Saharan African countries. We find that in comparison to traditional remittances sending channels, mobile money transfer channels are often superior in terms of service-related features as costs of transfers for sending and receiving households, speed of delivery, availability and access to the remittances by receiving households or security of transactions. More importantly, mobile cash systems can fulfil the SDG goal of the 3 per cent fee more than 10 years earlier than envisaged in 2030. On the other side, the choice to use a specific transfer channel might be restricted by the lack of physical and technological availability of providers and means, and technological illiteracy. In addition, sending and receiving households might be cautious to use mobile cash systems due to a lack of trust in the system, the providers or regulatory authorities. Accordingly, financial inclusion beyond e-payments and outreach to the poor is not an automatism. In contrast, the use of Bitcoin-based transfer systems is more ambivalent; these systems are technically more challenging both in terms of infrastructure and literacy and more vulnerable to fraud. Some findings also indicate that Bitcoin is an incomplete and inferior substitute to which migrants refer to if their first option is not available or suffers from severe deficiencies. Future research also needs to differentiate sending and receiving households stronger according to personal features in order to deepen our understanding about the choices of and restrictions of vulnerable groups who would benefit the most from using mobile cash systems.
Keywords: F24; G23; G28; O16; O19; 330; Remittances; Financial Inclusion; Bitcoin; Alternative Money; Financial Technology; Africa; Mobile Cash